IMPLEMENTATION OF 2 STAY 2 STRAY MODEL IN LEARNING THE CONCEPT OF alpha, Beta, AND Gamma RADIATIONS - Kana Puspita; Muhammad Nazar; Rakhmi Fitriana (FKIP USK, 2021)
The two stay two stray cooperative learning model basically emphasizes students to work together in groups, and provides opportunities for groups to share the results and information obtained with other groups, so that the learning process will be student-centered. This study aims to achieve optimum student learning activities through the application of the Two Stay Two Stray (TSTS) model in learning the concepts of alpha, beta and gamma rays, and to describe the student's response to the TSTS cooperative learning that has been implemented. The method used is quantitative with the pre-experimental research model type one shot case study. A total of 26 students taking radiochemistry courses were the subjects of this study. Research data were collected through student activity observation sheets during lectures and a student response questionnaire consisting of 10 statements. The results of observations on student activities show that the aspect of explaining in the lecture material, the aspect of cooperation between colleagues, and the activity of answering questions, respectively, have a value of 86, 85 and 90 percent. In general, students' positive responses to the application of the TSTS model were 95%. From the research results, it can be concluded that the implementation of TSTS is very effective in increasing student learning activities, making students happy in learning, and fostering self-confidence in learning.